2003
DOI: 10.1520/jfs2002043
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of External Blind DNA Proficiency Testing. II. Experience with Actual Blind Tests

Abstract: The background and goals of a national study to determine the feasibility of blind proficiency testing in U.S. forensic DNA laboratories are discussed. Part of the project involved designing and executing a series of fifteen blind proficiency tests. Execution included biological specimen donor recruitment and case evidence manufacturing. Simulated cases were submitted to DNA laboratories by law enforcement agencies and in some cases by other forensic-science laboratories. Replicate-manufactured evidence was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Various approaches have been developed to prepare capillary precolumns for nano-flow LC systems, including packed precolumns [9,10], polymer and silica monolithic precolumns [11] and particle-entrapped precolumns by monoliths [5,12]. Although monolithic or particle-entrapped monolithic precolumns are fritless, simplifying the column preparation, such columns suffer from the drawbacks, for example, polymer monolith could not endure high organic solvent, while silica monolith is prone to shrinking and cracking during column drying.…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches have been developed to prepare capillary precolumns for nano-flow LC systems, including packed precolumns [9,10], polymer and silica monolithic precolumns [11] and particle-entrapped precolumns by monoliths [5,12]. Although monolithic or particle-entrapped monolithic precolumns are fritless, simplifying the column preparation, such columns suffer from the drawbacks, for example, polymer monolith could not endure high organic solvent, while silica monolith is prone to shrinking and cracking during column drying.…”
Section: Introductionmentioning
confidence: 99%
“…Blind proficiency tests have been criticized as being expensive Peterson et al (2003aPeterson et al ( , 2003b. conducted a proof of principle to determine whether blind proficiency tests are feasible.…”
mentioning
confidence: 99%
“…(2003a, 2003b) conducted a proof of principle to determine whether blind proficiency tests are feasible. They concluded that for DNA laboratories samples could be manufactured (2003b: 39) and that the expected cost per test would be $2,000 to $3,500 and that economies could be achieved with two tests per laboratory (150 DNA laboratories) (2003a: 40), with a total cost for the two tests per laboratory of $630,000 to $1,035,000 per year. Koppl (2010) states ‘.…”
mentioning
confidence: 99%